2006
DOI: 10.2353/ajpath.2006.060602
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-Derived Tumor Necrosis Factor Can Promote Nerve Fiber Elongation in the Skin during Contact Hypersensitivity in Mice

Abstract: In humans, lesions of contact eczema or atopic dermatitis can exhibit increases in epidermal nerves, but the mechanism resulting in such nerve elongation are not fully understood. We found that contact hypersensitivity reactions to oxazolone in mice were associated with significant increases in the length of nerves in the epidermis and dermis. Using genetically mast cell-deficient c-kit mutant mice selectively repaired of their dermal mast cell deficiency with either wild-type or tumor necrosis factor (TNF)-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 63 publications
4
78
0
1
Order By: Relevance
“…Some of the positive immunomodulatory functions of mast cells that have been proposed based on in vitro studies have been confirmed in vivo using mast cell knock-in mice 1,54,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] or in mice lacking specific mast-cell-associated proteases [26][27][28][32][33][34] or lacking specific protease enzymatic activity 11 (Table 1 ). In many of these studies, the end points assessed included the recruitment of particular immune cells, such as granulocytes 28,32,33,[57][58][59][60][61]63,64,[67][68][69][70] , DCs 62,64,65,71 or various subpopulations of lymphocytes 64,67,70,72 .…”
Section: Positive Immunomodulatory Functions In Vivomentioning
confidence: 93%
See 1 more Smart Citation
“…Some of the positive immunomodulatory functions of mast cells that have been proposed based on in vitro studies have been confirmed in vivo using mast cell knock-in mice 1,54,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] or in mice lacking specific mast-cell-associated proteases [26][27][28][32][33][34] or lacking specific protease enzymatic activity 11 (Table 1 ). In many of these studies, the end points assessed included the recruitment of particular immune cells, such as granulocytes 28,32,33,[57][58][59][60][61]63,64,[67][68][69][70] , DCs 62,64,65,71 or various subpopulations of lymphocytes 64,67,70,72 .…”
Section: Positive Immunomodulatory Functions In Vivomentioning
confidence: 93%
“…In many of these studies, the end points assessed included the recruitment of particular immune cells, such as granulocytes 28,32,33,[57][58][59][60][61]63,64,[67][68][69][70] , DCs 62,64,65,71 or various subpopulations of lymphocytes 64,67,70,72 . Many of these studies also demonstrated that the lack of mast cells 54,[57][58][59][60][61][62][63][64]67,69,70 or a specific mast-cell product 28,32,33,54,60,63,67,68,70 also reduced the pathology associated with the immune response or impaired its effectiveness in promoting host resistance to infection.…”
Section: Positive Immunomodulatory Functions In Vivomentioning
confidence: 99%
“…Mast cells were identified with rhodamine-conjugated avidin (Vector; 1/1000). This method has been shown to effectively and selectively label mast cells in mouse skin tissue (8,24). All secondary Abs were 1/500 diluted in blocking solution.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The fact that there is a close association between mast cells and peripheral nerves may help explain why allergic inflammation in particular is so adept at evoking such neuronal responses (1,2). It is rather well established that allergen-induced activation of tissue mast cells is associated with alterations in the phenotype or physiology of nearby primary afferent (sensory) nerves (3)(4)(5)(6)(7)(8)(9)(10). Some effect of mast cell activation on these nerves can be explained by defined mast cell mediators such as histamine, cys-leukotrienes, PGD2, and tryptase (3,4,10,11).…”
mentioning
confidence: 99%
“…Products of arachidonic acid metabolism, such as cysteinyl leukotrienes and prostaglandins, influence the local environment involving nerves (51). Cytokines including TNF-α and growth factors, such as NGF, cause changes in local nerves so as to lower their threshold to activation and promote nerve fiber elongation (52)(53)(54)(55). Because nerves release the neuropeptides such as substance P and CGRP on stimulation and mast cells express receptors for many neuropeptides (56)(57)(58)(59), nerve activation, in turn, results in mast cell activation, i.e., degranulation or secretion of mediators (60).…”
Section: Nerve-mast Cell Communicationmentioning
confidence: 99%